Final Report - Workshop on Personal Property Security Law Reform - David E Allan; Patrick Quirk; Nicole Martin (Bond Law Review)
Work on the reform of the law relating to personal property security law reform has been under way in Australia for more than 40 years. Although it has progressed sporadically, it has had a constant objective. That objective has been to streamline the multiple and complex system of State and federal laws and procedures, based on statute and case law, in order to develop an efficient and modern regime to reduce the uncertainty and cost of financing transactions against personal property. The category of property described as “personal” has increased in size and value over that time, and it now plays a much greater role in security for business finance. Advances in technology have made the task of developing an appropriate infrastructure more effective and straightforward. Changes in taxation laws have meant that there is less emphasis on the production and registration of documents for revenue purposes. Our economy has become more dependent on credit for growth at all levels.